2013
DOI: 10.1074/jbc.m113.484337
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effect of Class-selective Histone Deacetylase Inhibitors during Tissue Regeneration following Hindlimb Ischemia

Abstract: Background:No information is available about the effect of class-selective histone deacetylase inhibitors (DIs) following hindlimb ischemia. Results: Class I and class IIa DIs prevent/delay ischemic muscle reconstruction at different stages. Conclusion:Evidence is provided about a detrimental effect of DIs during normal muscle regeneration. Significance: The therapeutic relevance of class-selective DIs in hindlimb ischemia may be limited by adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Moreover, depending on their phosphorylation state, class IIa HDACs shuttle between the nucleus (dephosphorylated) and the cytoplasm (phosphorylated) [6]. Class IIa HDACs have a variety of nuclear and cytosolic targets, including MEF2 transcription factors, HIF1␣, STAT1, and fork-head box proteins [7] and are involved in diverse processes, such as cellular response to hypoxia [8], myogenesis [9], synaptic plasticity and memory formation [10], and tissue regeneration [11].…”
Section: Clinical Relevancementioning
confidence: 99%
“…Moreover, depending on their phosphorylation state, class IIa HDACs shuttle between the nucleus (dephosphorylated) and the cytoplasm (phosphorylated) [6]. Class IIa HDACs have a variety of nuclear and cytosolic targets, including MEF2 transcription factors, HIF1␣, STAT1, and fork-head box proteins [7] and are involved in diverse processes, such as cellular response to hypoxia [8], myogenesis [9], synaptic plasticity and memory formation [10], and tissue regeneration [11].…”
Section: Clinical Relevancementioning
confidence: 99%
“…Because 48 hours of exposure damaged approximately 50% of cells, this time point was chosen for all experiments unless stated otherwise. To investigate the role of a specific class of HDACs involved in A1254-induced toxicity, cells were treated with the class I HDAC inhibitor MS-275 (Lanzillotta et al, 2013;Guida et al, 2014) and the class II HDAC inhibitor MC-1568 (Nebbioso et al, 2010;Spallotta et al, 2013;Guida et al, 2014) at 0.05, 0.5, and 5 mM. MTT assays showed that cell viability significantly improved in a dose-dependent manner when cells were pretreated with MS-275, as opposed to cells exposed to A1254 alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported in a mouse model of hindlimb ischaemia that the inhibition of class IIa HDACs is pro-angiogenic while class I HDAC inhibition is anti-angiogenic in mouse models of hindlimb ischemia [75].…”
Section: Peripheral Artery Diseasementioning
confidence: 99%